ANALISIS DIALEL KARAKTER UKURAN BUAH PEPAYA MENGGUNAKAN METODE I DAN II GRIFFING - Fatria, Dewi; Noflindawati, nFN; Budiyanti, Tri (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2017)
Problems in the assembly of hybrid papaya for improving fruit size is limited information of proper parents, a good hybrid combination and limited other genetic information. The aim of the research is to analyse general combining ability (GCA), specific combining ability (SCA) and the analysis of genetic characteristics related to the character of the size of the fruit on the five parents papaya using Griffing methods I and II approach. The study was conducted from January 2010 to December 2013. The full diallel population and half diallel population genetic material using five parenst of papaya. Papaya parents used were Merah Delima (BT-1), BT-2, Carmina, Carmida (BT-4) and Dampit. Research was arranged in a randomized block design with three replications. The results showed that there was a significant reciprocal effect on Griffing model method 1 causing different values of SCA in the same combination of crosses. There were no differences in GCA estimation values using Griffing Methods I and II. Parent Dampit has the highest positive GCA predictive value, while the BT-2 and BT-3 have negative GCA estimation values for all fruit size characters. Based on the SCA estimation using Griffing Method I, the crossed pair has the highest SCA guess value of BT-4xD and BT-1X D. When using the griffing method II, the crossed pairs of BT-3 x BT-4 and D x BT-4 have the largest SCA estimated value for fruit size. Based on the griffing method I and II, it is known that more fruit size characters are controlled by the additive gene, so improving the fruit character can be through the selection.